Development Information Geospatial System Application to Determine the Location of the Program Indonesia Pintar (PIP) - Fitria Rachmawati; Dahlia Widhyaestoeti; Zulkarnaen Noor Syarif; Nadia Putri Purnama; Adam Syah (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2024)
Through the Kartu Indonesia Pintar (KIP), the Program Indonesia Pintar (PIP) provides educational resources to school-age children (ages 6 to 21) that come from the miskin's household, including those who own Kartu Keluarga Sejahtera (KKS), Program Keluarga Harapan (PKH), orphan, people with disabilities, and victim of natural disaster. PIP is a component of the Bantuan Siswa Miskin program's purification (BSM). This information system was created to determine the location of Program Indonesia Pintar recipients using data in the Peta format. The use of this system will assist schools in providing students with timely and accurate instruction. The application that functions as this information system uses Google Maps to determine the latitude and longitude coordinates. During the COVID-19 pandemic, the government has reduced some types of aid to be distributed to the general public.